 ×     #### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping ```Solved Examples on Parabola Parabola is an important head under coordinate geometry. It often fetches good number of questions in various competitive examinations like the JEE.

Example 1:

Three normals are drawn from the point (c, 0) to the curve y2 = x. Show that c must be greater than ½. One normal is always the x-axis. For what value of ‘c’ are the other two normals perpendicular to each other? (IIT JEE 1991)

Solution:

We know that the normal of a parabola is y = mx – 2am – am3.

Hence, the equation of normal for y2 = x is y = mx – m/2 – m3/4

Since the normal passes through (c, 0), we have

mc – m/2 – m3/4 = 0

This gives m(c – 1/2 – m2/4) = 0

This yields either m = 0 or m2 = 4(c-1/2)

For m = 0, the equation of normal is y = 0.

Also, m2 ≥ 0, so c-1/2 ≥ 0 or c ≥ ½.

At c = ½, we have m = 0.

For the other normals to be perpendicular to each other, we must have m1m2 = -1.

m2/4(1/2 – c) = 0 has m1m2 = -1.

This means (1/2 - c)/1/4 = -1.

This gives c = ¾.

Example 2:

Normals are drawn from the point P with slopes m1, m2, m3 to the parabola y2 = 4x. If locus of P with m1m2 = α is a part of parabola itself, then find α. (IIT JEE 2003)

Solution:

The equation of the normal to the parabola y2 = 4ax.is y = mx – 2am – am3.

Hence, the equation of the normal to the parabola y2 = 4x is y = mx – 2m – m3.

Now, if it passes through (h, k), then we have k =  mh – 2m – m3

This can be written as m3 + m(2-h) + k = 0 …. (1)

Here, m1 + m2 + m3 = 0

m1m2 + m2m3 + m3m1 = 2 - h

Also, m1m2m3 = -k, where m1m2 = α

Now, this gives m3 = -k/α and this must satisfy equation (1).

Hence, we have (-k/α)3 + (-k/α)(2-h) + k = 0

Solving this, we get k2 = α2h – 2α2 + α3

And so we have y2 = α2x – 2α2 + α3

On comparing this equation with y2 = 4x we get

α2 = 4 and -2α2 + α3 = 0

This gives α = 2.

Example 3:

Find the equation of the parabola whose focus is (3, –4) and directrix is the line parallel to 6x – 7y + 9 = 0 and directrix passes through point (3/2,2).

Solution:

Let (x, y) be any point on the parabola. Then by definition, the distance between (x, y) and the focus (3, – 4) must be equal to the length of perpendicular from (x, y) on directrix. So first we will find the equation of the directrix.

The line parallel to 6x – 7y + 9 = 0 is  6x – 7y + 6 = 0 …… (1)

Since directrix passes through (3/2,2), this point wil satisfy equation (1) and hence 6(3/2) – 7(2) + k = 0

⇒ k = – 9 + 14 = 5.

Equation of directrix is 6x – 7y + 5 = 0

Now by definition of parabola,

√({(x – 3)2 + (y + 4)2}) = (6x – 7y + 5)/√(62 + 72)

⇒ 85{(x – 3)2 + (y + 4)2} = (6x – 7y + 5)2

⇒ 49x2 + 36y2 + 84xy – 570x + 750y + 2100 = 0

Example 4:

Find the equation of the parabola whose directrix makes an isosceles right angled triangle of area 4 square units with the axis in the 3rd quadrant and focus is on the line y = x, 2 units away from the origin.

Solution:

First we find the equation of directrix. Let the directrix form the isosceles triangle OAB with OA = OB = a.

Then according to the given condition, ar (? OAB) = 4

⇒ 1/2 a2= 4

⇒ a = ± 2√2 {? the triangle in 3rd quadrant so =-2√2}

Therefore the co-ordinate, of A and B are (–2√2, 0) and (0, –2√2) respectively.

So, equation of directrix

(y – 0) = ((0+2√2)/(-2√2-0)) (x + 2√2) ⇒ x + y + 2√2 = 0

Now the focus S is on line y = x and 2 units away from the origin i.e. OS = 2 ⇒ point (√2, √2) by definition of parabola, we have

√((x-√2)2 + (y-√2)2) = |(x+y+2√2)/√(12+12)|

⇒ x2 + y2– 8√2x – 8√2y – 2xy = 0.

Example 6:

At any point P on the parabola y2 - 2y – 4x + 5 = 0, a tangent is drawn which meets the directrix at Q. Find the locus of point R, which divides QP externally in the ratio 1/2:1.(IIT JEE 2004)

Solution:

The given parabola is y2 - 2y – 4x + 5 = 0.

This can be rewritten as (y-1)2 = 4(x-1)

Its parametric coordinates are x-1 = t2 and y -1 = 2t and hence we have P(1 + t2, 1 + 2t)

Hence, the equation of tangent at P is

t(y-1) = x – 1 + t2, which meets the directrix x = 0 at Q.

Hence, y = 1 + t – 1/t or Q(0, 1 + t – 1/t)

Let R(h, k) be the point which divides QP externally in the ratio 1/2:1. Q is the mid-point of RP

So, we have 0 = (h + t2 + 1)/2 which gives t2 = – (h + 1) …. (1)

and 1 + t – 1/t = (k + 2t + 1)/2 which gives t = 2/(1- k) ….. (2)

Hence, from equations (1) and (2) we get, 4/(1-k)2 + (h + 1) = 0\or (k-1)2(h +1) + 4 = 0

Hence, the locus of a point is

(x + 1)(y - 1)2 = 0.

Example 7:

Find the equation of the common tangents to the parabola y2 = 32x and x2 = 108y.

Solution:

The equation of the tangent to the parabola y2 = 4ax, is

y = mx + a/m …… (1)

The equation of tangent to the parabola y2 = 32x …… (2) is

y = mx + 8/m …… (3)

If this line given by (3) is also a tangent to the parabola x2 = 108y, then (3) meets x2 = 108y …… (4)  in two coincident points

⇒ Substituting the value of y from (3) in (4) we get  x2 = 108 [mx + (8/m)]

⇒ mx2 – 108m2x – 864 = 0

The roots of this quadratic are equal provided b2 = 4ac.

i.e. (– 108 m2)2 = 4m (–864)

⇒ m = (-2)/3 (m ≠ 0, from geometry of curves)

Substituting their value of m in (3), the required equation is

y = (-2)/3 x + 8/(–2/3)

y = (-2)/3 x – 12

⇒ 2x + 3y + 36 = 0

Example 8:

Find the angle of intersection of the parabola y2 = 8x and x2 = 27y.

Solution:

The given parabolas are y2 = 8x …… (1)

and x2 = 27y …… (2)

Solving (1) and (2) we get

(x2/27)2 = 8x

⇒ x4 = 5832 x

⇒ x4 – 5832 x = 0

⇒ x(x3 – 5832) = 0

⇒ x = 0, x = 18

Substituting these values of x in (2) we get y = 0, 12

The point of intersection are (0, 0), (18, 12).

Now, we consider these points one by one

At the point (0, 0)

y2 = 8x ⇒ dy/dx = 4/y ⇒ dy/dx|(0,0) = ∞

x2 = 27y ⇒ dy/dx = 2x/27 ⇒ dy/dx|(0,0) = 0

⇒ The two curves intersect at the point (0, 0) at right angle.

At the point (18, 12)

y2 = 8x ⇒ dy/dx|(18,12) = 4/12 = 1/3 = m1 (say)

x2 = 27y ⇒ dy/dx = 2x/27 ⇒ dy/dx|(18,12) = (2×18)/27 = 4/3 = m2 (say)

Let θ be the angle at which the two curves intersect at the point (18, 12)

Then tan θacute = |(m2 - m1)/(1 + m1 m2)| = 3/13

θacute = tan-1 (3/13).

Example 9:

Prove that (x + a)2 = (y2 - 4ax), is the locus of the point of intersection of the tangents to the parabola y2 = 4ax, which includes an angle π/4.

Solution: Let two tangent to the parabola y2 = 4ax …… (1)

be yt1 = x + at12…… (2)

and yt2 = x + at22  …… (3)

Let the point of intersection of the tangent be (x1, y1) then solving equation (1) and (2) we get, x1 = at1t2

y1 = a(t1 + t2)

Also the slope of these tangents are 1/t1 and 1/t2

∴ If α be the angle between these two tangents then

tan α = + (m1 - m2)/(1 + m1m2) = (±(1/t1 -1/t2))/(1 + 1/t1 × 1/t2).

⇒ tan α = ± ((t2 - t1)/(1 + t2t1))

We are given α = π/4

∴ tan π/4 = 1 = ± ((t2 - t1)/(1 + t2t1))

⇒ (1 + t1t2)2 = (t2 – t1)

⇒ {1 + (x1/a)2} = (t1 – t2)2 – 4t1t2 = (y1/a)2 - 4x1/a

⇒ (x1 + a)2 = y12– 4ax1

⇒ Required locus of (x1, y1) is (x + a)2 = (y2 - 4ax).

Example 10:

If two tangents to a parabola intercept a constant length on any fixed tangent, find the locus of their point of intersection.

Solution:

Let yt = x + at2 …… (1)

be a fixed tangent to the parabola y2 = 4ax …… (2)

Let the other two tangent to (2) be yt1 = x + at12…… (3)

And yt2 = x + at22…… (4)

The point of intersection of (1) with (3) and (4) are P {att1, a(t1 + t2)} and Q{at t2, a (t + t2)}

Given PQ is constant or PQ2= constant

⇒ a2t2 (t1 – t2)2 + a2(t1 – t2)2 = constant

⇒ a2(t2 + 1) (t1 – t2)2= constant

⇒ (t1 – t2)2 = constant since t is constant as (1) is a fixed tangent.

⇒ (t1 – t2)2 = c (say) …… (5)

Let (x1, y1) be the point of intersection of (3) and (4),

then x1 = at1t2 and y1 = a(t1 + t2) …… (6)

We know that

(t2 – t1)2 = (t1 + t2)2

From equation (5), (6) and 97) we get

c = (y1/a)2- 4x1/a  or y12 = 4x1 a – a2

c = 4a (x1 + 1/4 ac)

⇒ the locus of (x1, y1) is  y2 = 4a (x + ¼ ac)

⇒ The required locus is a parabola whose latus rectum is 4a i.e. equal to latus rectum of y2 = 4ax.

Illustration 11:

Find the locus of the poles of normals to parabola y2 = 4ax. Solution:

Any normal to the parabola y2 = 4ax is …… (1)

y = mx – 2am – am3 …… (2)

Let (x1, y1) be the pole of (2) with respect to (1), then (2) is the polar of (x1, y1) w.r.t (1)  i.e.

yy1 = 2a (x + x1) comparing (2) & (3), we get  2a/m = y1/1 = (2ax1)/(-2am – am3)

Hence we get  x1 = –2a – am2…… (4)

and y1 = 2a/m …… (5)

Eliminating m between (4) & (5) we get y12(x1 + 2a) + 4a3 = 0

∴ The required locus of (x1, y1) is  (x + 2a)y2 + 4a3 = 0

Illustration 12:

If the line x -1 = 0 is the directrix of the parabola y2 – kx + 8 = 0, then one of the values of k is (IIT JEE 2000)

Solution:

The given parabola is y2 – kx + 8 = 0.

This can be written as y2 = kx - 8

This gives y2 = k (x - 8/k)

Shifting the origin we get Y2 = kX, where Y = y and X = x-8/k

The directrix of the standard parabola is X = -k/4

The directrix of the original parabola is x = 8/k – k/4

Also, x = 1 coincides with x = 8/k – k/4.

On solving these we get k = 4.

Illustration 13:

A tangent to the parabola y2 + 12x = 0 cuts the parabola y2 = 4ax at P and Q. Find the locus of middle points of PQ.

Solution:

Any tangent to the parabola y2 = – 4bx is y = mx – b/m

y = mx – 3/m

Let (x1, y1) be the mid point of PQ, where P and Q are point of intersection o line (1) and y2 = 4ax

Equation of chord PQ is

S1 = T

y12 – 4ax1 = y1y – 2a(x + x1)

y1y – 2ax – y12 + 2 ax1 = 0 …… (2)

Equation (1) can be written as

my – m2x + 3 = 0 …… (3)

equation (2) and (3) represent the same line

⇒ m/y1 = m2/2a = 3/(2ax1 - y12) …… (4)

⇒ m = 2a/y1 (from 4)

Again, from (4), we get

m/y1 = 3/(2ax1 - y12 )

⇒ 2a/y1 = 3/(2ax1 - y12 )

⇒ Locus of (x1, y1) is  4a2x = y2 (3 + 2a)

Illustration 14:

The point of intersection of the tangents at the ends of the latus rectum of the parabola y2 = 4x is ..?(IIT JEE 1994)

Solution:

The coordinates of the xetremities of the latus rectum of y2 = 4ax are (1, 2) and (1, -2).

The equations of tangents at these points are gievn by

y.2 = 4(x+1)/2

This gives 2y = 2(x + 1)...... (1)

and y(-2) = 4(x+1)/2

which gievs -2y = 2(x + 1) ….. (2)

The points of intersection of these tangents can be obtained by solving these two equatiosn simultaneously.

Therefore, -2(x +1) = 2(x + 1)

which gives 0 = 4(x +1)

this yields x = -1 and y = 0.

Hence, the required point is (-1, 0).

Illustration 15:

The normal at any point P of the y2 = 4ax meets the axis in G and to the tangent at the vertex at H. If A be the vertex and the rectangle AGQH be completed, prove that the locus of Q is x3 = 2ax2 + ay2.

Solution:

Any normal to the parabola y2 = 4ax … (1)

is y = mx – 2am – am3 … (2)

This normal (2) meets the axis y = 0 of (1) in G and the tangent at the vertex i.e. x = 0 in H

∴ The coordinates of G and H are (2a + am2, 0) and (0, –2am – am3) respectively. Also the vertex A is (0, 0). Let Q be (x1, y1)

Given that AGQH is a rectangle. AQ and GH are its diagonals and therefore there mid points are same. Now the mid point of AQ is (1/2 x1,1/2 y1 ) and that of GH is  [1/2 (2a + am2+0) 1/2 (0-2am-am3 ) ]

i.e. [1/2 (2a+am2 )-1/2 (2am+am3 ) ]

⇒ The mid points coincide so we have

1/2 x1 = 1/2 (2a + am2), 1/2 y1 = -1/2 (2am + am3)

or x1 = 2a + am2, y1 = – (2am + am3)

The required locus of Q is obtained by eliminating m between these.

Now y12 = (m2a2) (2 + m2)2 = a (m2a) [2 + am2/a]2 = a(x1 – 2a) (x1/a)2

⇒ ay12 = (x1 – 2a) x12

So the locus of Q is ⇒ ay2 + 2ax2 = x3

Related Resources:

You may wish to refer working rule to calculate area.

For getting an idea of the type of questions asked, refer the previous year papers.

To read more, Buy study materials of Parabola comprising study notes, revision notes, video lectures, previous year solved questions etc. Also browse for more study materials on Mathematics here.
```  ### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution 